Design of Local Heat Treatment for Crack Retardation in Aluminium Alloys. (2015) - Groth, Anne; Horstmann, Manfred; Kashaev, Nikolai; Huber, Norbert
Abstract: Residual stresses introduced by laser heating can be used to improve the damage tolerance behaviour of lightweight structures. In this study the efficiency of a novel design was analysed, namely the application of dashed line patterns. The samples were prepared out of sheets of AA2024 T3 alloy. Two lines applied symmetrically on M(T)200 specimens resulted in an increase in fatigue lifetime of about 20% in comparison to the untreated material. The corresponding improvement by using continuous lines in the same geometry and material was only 10%. The application of a second set of lines increased the total improvement to 20% in the case of continuous lines while no further improvement of the value of 20% in the case of dashed lines was achieved.